Decomposing blazar spectra into lepto‐hadronic emission components. Issue 5 (10th September 2018) - Gokus, A.; Richter, S.; Spanier, F.; Kreter, M.; Kadler, M.; Mannheim, K.; Wilms, J.
Abstract : The recently reported coincidences between high‐energy neutrino events and major blazar outbursts reinforce the relevance of lepto‐hadronic emission models for blazars. We study the influence of physical parameters on the neutrino output by modeling blazar spectral energy distributions self‐consistently assuming a relativistically propagating acceleration zone surrounded by a larger cooling zone. We find that the gross features of the spectral energy distribution can readily be explained with the model. A rigorous test requires time‐resolved measurements of blazar spectral energy distributions during an outburst and high‐statistics neutrino measurements to discriminate the leptonic and hadronic emission components.